2022
DOI: 10.1177/23969873221099736
|View full text |Cite
|
Sign up to set email alerts
|

European Stroke Organisation (ESO) guidelines on management of unruptured intracranial aneurysms

Abstract: Unruptured intracranial aneurysms (UIA) occur in around 3% of the population. Important management questions concern if and how to perform preventive UIA occlusion; if, how and when to perform follow up imaging; and non-interventional means to reduce the risk of rupture. Using the Standard Operational Procedure of ESO we prepared guidelines according to GRADE methodology. Since no completed randomised trials exist, we used interim analyses of trials, and meta-analyses of observational and case-control studies… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
30
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 85 publications
0
30
0
1
Order By: Relevance
“…Aneurysm growth is a significant risk factor for rupture [ 2 , 3 , 4 , 5 , 6 , 7 ]; Brinjijki et al reported growing IAs are more than 30 times more likely to rupture compared to stable IAs [ 5 ]. Aneurysm growth currently is assessed by repeat cerebral vascular imaging, typically by computed tomography angiography, magnetic resonance imaging, or digital subtraction angiography [ 8 ], which can be expensive and depending on the modality, may carry potential risks.…”
Section: Introductionmentioning
confidence: 99%
“…Aneurysm growth is a significant risk factor for rupture [ 2 , 3 , 4 , 5 , 6 , 7 ]; Brinjijki et al reported growing IAs are more than 30 times more likely to rupture compared to stable IAs [ 5 ]. Aneurysm growth currently is assessed by repeat cerebral vascular imaging, typically by computed tomography angiography, magnetic resonance imaging, or digital subtraction angiography [ 8 ], which can be expensive and depending on the modality, may carry potential risks.…”
Section: Introductionmentioning
confidence: 99%
“…Unruptured intracranial aneurysms (UIA) cause subarachnoid hemorrhage once bleeding, resulting in severe poor clinical outcomes. The risk of rupture in UIA significantly decreases after receiving endovascular treatment or surgical clipping in cases of aneurysm growth (1,2). Inflammation plays a vital role in the development and progression of intracranial aneurysms (IA), which can be reflected by aneurysm wall enhancement (AWE) on high-resolution vessel wall magnetic resonance imaging (HR-VWI) (3)(4)(5)(6)(7)(8).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, decision making regarding the best managing options for patients with UIAs is very difficult. In the very recent European Stroke Organization (ESO) guidelines on management of unruptured intracranial aneurysms, it has been suggested that, in adult patients in whom the estimated 5 years risk of aneurysm rupture is higher than the risk of preventive treatment, the latter should be proposed, considering the most effective and safe modality for that particular aneurysm [ 6 ]. In the same guidelines, the authors suggested considering aneurysm morphology and complexity as important factors when balancing between conservative and preventive treatment [ 6 ].…”
Section: Introductionmentioning
confidence: 99%
“…In the very recent European Stroke Organization (ESO) guidelines on management of unruptured intracranial aneurysms, it has been suggested that, in adult patients in whom the estimated 5 years risk of aneurysm rupture is higher than the risk of preventive treatment, the latter should be proposed, considering the most effective and safe modality for that particular aneurysm [ 6 ]. In the same guidelines, the authors suggested considering aneurysm morphology and complexity as important factors when balancing between conservative and preventive treatment [ 6 ]. In fact, despite advancement in surgical and endovascular techniques, the treatment of complex intracranial aneurysms still poses significant difficulties for vascular neurosurgeons and interventional neuroradiologists [ 7 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%